KONSEP TASAWUF SEBAGAI PSIKOTERAPI BAGI PROBLEMATIKA MASYARAKAT MODERN (Study Terhadap Kitab Ihya’ ‘Ulumiddin Karya Imam Al-Ghazali) - Nur Cholis; Syahril Syahril (Manthiq, 2018)
The life of the modern age has resulted in some human beings engulfed by spiritual emptiness, advances in the field of science, technology and philosophy of rationalism unable to fulfill the basic human need in the aspect of transcendental values, if it is not matched by spiritual planting in the soul, consequently the human soul will become dry and empty, causing problems in life. In this case Sufism appears by bringing a psychotherapist concept to the problems that arise in the soul of modern society. As for the concept of tasawuf which the author offers here is tasawuf Imam Al-Ghazali in Ihya „‟ Ulumiddin. The problems discussed in this research are how the teachings of Sufism of Al-Ghazali, how the problems of modern society, and how tasawuf Al-Ghazali can become psychotherapy for the problems of modern society. This study is a study taken from primary sources namely Ihya „‟ Ulumuddin and other supporting sources. This research uses descriptive qualitative approach with the type of library research study (library research). That is by reviewing the book or primary and secondary sources with regard to the issues discussed, the method of discussion used is descriptive analysis.The result of this study is that the problems of modern society can be grouped into five parts: moral degradation, spiritual emptiness, loss of value and meaning of life, sters and frustration, and loss of self-esteem and future. Therefore, Sufism is indispensable in modern life, because in this era many human beings are starting to leave the spiritual aspects or worship to their God, they are many who began to forget its existence as a servant of God, so there are many problems in life. Psychotherapy given to the problems are: (1) repentance is back to the right path, regret the wrong actions and will not repeat it again, (2) riyadhah and mujahadah is continuously doing the exercises and earnestly to return to Allah, (3) Zuhud is to use the facilities of the world by not defeating the affairs of the Hereafter, (4) Patience is not always impose the will and able to live the provisions of God during life in the world, and (5) tawakkal ie submit all the results of efforts that have done only to God and always prejudiced both of Him.